Effects of saxagliptin on postmenopausal osteoporosis in rats: an investigation into its anti-inflammatory and anti-osteoporotic properties - Marwa Harb; Abdel Rahman Yassin; Essam Ghayaty; Basma Hamed; Neimat Yassin (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Saxagliptin (SAXA) is one of the dipeptidyl peptidase-4 inhibitors (DPP-4i), awidely used drug class in the management of type 2 diabetes mellitus (T2DM).Through modulating cytokine production, DPP-4i appear to exhibit anti-inflammatory benefits. Worldwide, up to one-third of women over 50 suffer from postmenopausal osteoporosis (OP), which is abone condition that makes affected bones susceptible to fractures. In postmenopausal OP, estrogen deficiency enhances the inflammatory cytokine production, promoting bone resorption. The central focus of this study was to explore the possible impacts of SAXA on bone remodeling and inflammation in a rat model of OP, and to compare these effects with those of calcitonin (CT). Materials and methods: For the induction of OP, the two ovaries of female Sprague-Dawley rats were removed. Two weeks post-ovariectomy (OVX), rats of the CT group, the SAXA group, and the SAXA-CT combination therapy group started to receive CT (5 U/kg/d, 5 days/week, by S.C. injections), SAXA (2 mg/kg/d, by oral gavage), and combination therapy, respectively, from the 15th day post-OVX and lasted for 4 weeks. Then, all rats were euthanized. Serum Procollagen type I N propeptide (PINP) as a marker of bone formation, carboxy-terminal telopeptide of type I collagen (CTX-I) as a marker of bone resorption, and tumor necrosis factor-α (TNF-α) were assayed, with histological examination of femoral bone sections. Results: OVX caused a notable deterioration in bone histopathology, a substantial decrease in serum PINP, a substantial increase in serum CTX-I, and a marked elevation of serum TNF-α levels relative to the sham group. All these findings were significantly reversed by CT, SAXA, and combination therapy, with the latter group showing the most significant results. Conclusion: SAXA suppressed TNF-α, leading to anti-osteoporotic and anti-inflammatory effects that ameliorated OVX-induced OP.